1982
DOI: 10.1007/bf00343314
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to cell-mediated cytotoxicity is correlated with reduction of H-2K gene products in AKR leukemia

Abstract: AKR leukemia cell lines differing in the amount of H-2K and H-2D antigens expressed on the cell surface were used to assess cell-mediated immune responses in syngeneic mice against Gross/AKR murine leukemia virus (MuLV)-induced tumors. Leukemic cells with reduced expression of H-2Kk antigens were inactive as inducers of Gross-MuLV/H-2k-specific cytotoxic T lymphocytes (CTL) and resistant to lysis by CTL raised against H-2Kk positive AKR leukemia cells. H-2Kk positive leukemias induced cytotoxic effectors, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 22 publications
3
42
0
Order By: Relevance
“…Thymoma cell lines derived from tumors in ageing AKR mice have different abilities to form leukemias when reintroduced back into animals (14,47,49). Detailed analysis showed that tumorigenicity correlates with expression of MHC class I genes in the cell membrane (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thymoma cell lines derived from tumors in ageing AKR mice have different abilities to form leukemias when reintroduced back into animals (14,47,49). Detailed analysis showed that tumorigenicity correlates with expression of MHC class I genes in the cell membrane (47).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells frequently show quantitative alterations in their expression of H-2 molecules compared with cells from the corresponding normal tissues (11,16,46,52,57). Reduced expression of one or more H-2 antigens appears to be associated with the ability of tumor cells to escape surveillance by cytotoxic T lymphocytes and in some cases can facilitate metastatic spread (8,47,58).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of multiple retroviral insertions adult AKR mice often develop tumors, particularly thymomas. Tumor cells frequently show quantitative or qualitative alterations in their expression of class I molecules which is discussed to be a selective advantage for tumor progression (Jones and Bodmer 1980;Festenstein and Schmidt 1981;Schmidt and Festenstein 1982;Lampson et al 1983;Doyle et al 1985;Schmidt et al 1986). In particular, AKR derived leukemic T-cell lines have been shown to express new H-2 class I specificities (Labeta et al 1989).…”
Section: Comentioning
confidence: 99%
“…Major histocompatibility complex (MHC) class I molecules are known to play an important role in tumour growth and metastasis [1][2][3][4][5][6][7][8]. Several reports indicate that the level of MHC class I expression on the surface of tumour cells has a decisive influence on whether a tumour will be rejected or accepted when transplanted to histocompatible immunocompetent recipients [9][10][11].…”
Section: Introductionmentioning
confidence: 99%